When Disclosure Is Not Enough: The Divergent Effects of CSR Disclosure and CSR Investment on Corporate Performance in Emerging Market Manufacturing Firms - Fita Helmaliya Putri; Jon Kenedi (Universitas Pattimura, 2026)
This study examines the divergent effects of Corporate Social Responsibility (CSR) disclosure and CSR investment on corporate performance among basic materials and chemical manufacturing firms listed on the Indonesia Stock Exchange during 2021–2024. The study addresses the persistent inconsistency in the CSR–performance literature, which has largely treated CSR as a single construct while overlooking the distinction between symbolic disclosure and substantive investment. Using an explanatory quantitative design, secondary data were collected from annual reports, sustainability reports, and financial statements. Firm performance was measured by Return on Assets (ROA), Return on Equity (ROE), and Return on Sales (ROS). Panel regression analysis was employed to estimate the simultaneous and individual effects of CSR disclosure and CSR investment. The results reveal that CSR disclosure has a significant negative association with all three performance indicators, whereas CSR investment exerts a significant positive effect. These findings suggest that symbolic CSR disclosure primarily serves legitimacy purposes without directly generating economic value, while substantive CSR investment strengthens stakeholder relationships, enhances corporate reputation, and improves financial performance. This study contributes to the literature by conceptualizing CSR as two distinct dimensions—symbolic and substantive—and introducing the concept of CSR Performance Divergence, thereby extending stakeholder and legitimacy theories in explaining how different CSR mechanisms create corporate value.